A phase 2 study of inotuzumab ozogamicin and rituximab, followed by autologous stem cell transplant in patients with relapsed/refractory diffuse large B-cell lymphoma. Issue 10 (3rd October 2015) - Wagner-Johnston, Nina D.; Goy, Andrè; Rodriguez, Maria A.; Ehmann, W. Christopher; Hamlin, Paul A.; Radford, John; Thieblemont, Catherine; Suh, Cheolwon; Sweetenham, John; Huang, Yifan; Sullivan, Sharon T.; Vandendries, Erik R.; et al.
Abstract : This study evaluated the safety and efficacy of inotuzumab ozogamicin (INO), a targeted humanized anti-CD22 antibody conjugated to calicheamicin, plus rituximab (R-INO) every 3 weeks, up to six cycles, followed by high dose therapy and autologous stem cell transplant (HDT-aSCT) in patients with high-risk relapsed/refractory diffuse large B-cell lymphoma (DLBCL). The primary endpoint was overall response (OR) rate after three cycles of R-INO. Sixty-three patients were enrolled. Common grade 3/4 adverse events during R-INO treatment were thrombocytopenia, lymphopenia and neutropenia. OR rate after three cycles of R-INO was 28.6% (95% confidence interval: 17.9–41.4). Eighteen patients underwent HDT-aSCT; 2-year progression-free survival (PFS) for these patients was 61.1%. Serious infections and hepatic toxicity following aSCT occurred in 33% and 22%, respectively. One- and 2-year PFS rates for all enrolled patients were 28.9% and 25.3%, respectively (median, 3.0 months). R-INO had lower than expected activity as a salvage regimen for transplant eligible patients with DLBCL.